Backend de aplicación multiplataforma de aprendizaje personalizado para los estudiantes de la ESPAM MFL - Álava Santana, Dany Rolando (2023)
The purpose of this work was to develop the core/backend of the multiplatform application "Gamivity", which allows the teaching management of autonomous gamified activities, focused on the students at ESPAM MFL university. This platform has as its fundamental axis the integration of two general components: gamification and personalized learning driven by artificial intelligence. As regards the personalized experience, it was implemented through a Python library of a "sentence transformers" type model, which offered adequate performance to the needs of the system. For the construction of the backend, the agile methodology "Extreme Programming" was used, which, through its iterative phases, allowed the development flow to be executed satisfactorily. The first phase carried out was planning, in which the interview technique was used to gather requirements; later, thanks to the UML diagrams used, it was possible to model the system corresponding to the design phase. Consequently, it proceeded with the development of its core, making use of the "Microsoft Dot Net 6" framework. In the last phase, the respective tests were carried out to guarantee the integrity of the data and optimal operation of the system. The final product made it possible to manage the evaluation activities of the students by the ESPAM MFL teachers, as well as to offer a nucleus capable of satisfying the requests of the gamified mobile application.